Incidence of Facial Palsy and its Impact on Quality of Life of Patients - Fareena Ahmad, Mahwish Saeed, Iram Rani Hashmi, Muhammad Khurram Ilyas, Noor Fatima Haroon, Shamima Abdullah, Amina Tariq (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: This study was planned to assess the frequency of facial palsy in general population and its impact on the quality of life of patients. Method: This descriptive crossectional investigation was conducted in Neurology department of a tertiary care hospital of Lahore from March, 2021 to June, 2022. Sample size was 168 patients with facial palsy out of 246. Data was collected using purposive sampling technique. Frequencies and percentages were calculated for gender, incidence of facial palsy and quality of life. Mean and standard deviation was calculated for age. Results: Total number of patients had facial palsy were 168 out of 246 which was 68.29%. Males were 36.90% whereas females were 63.10%. Face palsy of left side was found among 34.25% patients and 65.75% patients had facial palsy of right side. Conclusion: Incidence rate of facial palsy was above average and patients reported poor quality of life after facial palsy. Keywords: Facial Palsy, Quality of Life, Depression, Facial nerve. INTRODUCTION Facial expression play an important role in having an influential interpersonal communication. In understanding this aspect, evolutionary1 as well as social2 point of view is involved at same pace. The generation of facial expressions are based on complex mechanisms of contraction of facial muscles while working in coordination under the influence of stimulus from brain via innervation on face.3 But due to the interruption in the functioning of facial nerve, a noteworthy facial movement may change which is quite problematic in having direct interpersonal communication.3 Facial expression could be affected due to several causes among which face palsy is the commonest.4-6 Other etiologies are neoplastic,7 lyme disease, otitis media7-9, traumatic11-12 and neurologic diseases.8,10 Clinical implications of face palsy has been assessed in numerous research investigations.13-15 It was reported in literature that for vestibular schwannoma patients, rehabilitation services can improve their quality of life.15 Incidence of facial palsy in Peshawar was reported in a research study was 56.63%.16 Literature is deficient in terms of incidence of facial palsy in general population of Pakistan, so there is need to assess the incidence of facial palsy in Pakistan. Therefore this study was planned to assess the frequency of facial palsy in general population and its impact on the quality of life of patients. METHODOLOGY This descriptive crossectional investigation was conducted in Neurology department of a Tertiary Care Hospital of Lahore from March, 2021 to June, 2022. Sample size was 168 patients of facial palsy. Data was collected using purposive sampling technique. The age of patients ranged from 18 years to 40years. After the ethical approval from the institution, permission was taken from medical superintendent and head of department for data collection. Before recruitment of patients for the study, written consent form was signed by all participants and brief introduction of the study was also given. Patients’ demographic data, clinical investigations and progress was taken. To assess the associated lifestyle factors, questionnaire to measure quality of life was used which had a dichotomous response recording way. Data was entered in SPSS version 25.0. Frequencies and percentages were calculated for gender, incidence of facial palsy and quality of life. Mean and standard deviation were calculated for age. RESULTS Total number of patients who had facial palsy were 168 out of 246 which turned out the sample to be 68.29%. Males were 36.90% whereas females were 63.10%. The mean age of patients was 26.6±4.13. Facial palsy of left side was found in 34.25% patients and